Stylistic-Interpretative Statistics of The Creation for Guitar Solo (Preludes no. 1-5) by Heitor Villa Lobos - Dragomirescu Daniel (Sciendo, 2019)
In the past, more precisely in the Fifteenth and Sixteenth centuries, both pieces for keyboard instruments (organ or clavecin) and those for the guitar's ancestor, the lute, were preceded by an introduction bearing the title of prelude. In the seventeenth century, this prelude was used as an introduction to some religious works, being synonymous to the preamble, as both were meant to prepare the atmosphere and tone of a musical piece. Johann Sebastian Bach played a decisive role in the evolution of the prelude, using it as the first part of the preclassic instrumental suite, with the intention of setting the unique tone, the tone in which the whole work will be performed. Later, in the 19th and 20th centuries, taking over the tradition of J.S.Bach, the composers will write cycle pieces for various instruments, which, through their rich, melodic, harmonic, rhythmic variety of form and genre, will enjoy success in the concert halls. Examples include the cycles of preludes of Frederich Chopin, Claude Debussy, Alexandr Skriabin, Serghey Rachmaninov, Mihail Jora, and others. Villa-Lobos preludes touch the audience's sensitivity more directly than studies. Their appearance is an essential contribution to the guitar repertoire of the 20th century. In the small form, the author proved a brilliant sense of balance, intense feelings, great conceptual originality, making the most of the technical and sound resources of the instrument. These short compositions, always present in the repertory of all great guitarists, require our attention and admiration. Written shortly before 1940, in the original manuscript these preludes were six. Unfortunately, one of them, "the best of all" as the composer said, was lost. As regards this statement, John Duarte, in his work, the Preludes of Villa-Lobos. Some notes" considers this would have an ironic character. "Just like the Three Musketeers who were actually four, so the 5 Preludes were originally six".143